DEVELOPMENT OF IT GOVERNANCE COMPETENCES IN THE BOARD OF DIRECTORS IN A DIGITAL ECONOMY - M. Nikishova; O. Suchkova (Вестник университета)
The need to develop competencies and involve experts in IT Governance issues to the boards of directors has been substantiated, as well as the recommendations for expanding the areas of responsibility of the board of directors in IT Governance issues have been developed, which should be included in the Russian Corporate Governance Code. The tendencies in the regulation of issues related to the development of digital technologies, the content of the Codes of Corporate Governance in several countries, the recommendations of Cobit 5.0, and the current competences of the board of directors have been analysed. The recommendations on expanding the areas of responsibility of the board of directors in the field of IT Governance have been developed. It has concluded, that IT Governance expertize in the board of directors becomes a necessity, without which companies can`t easily remain competitiveness in the era of the Fourth Industrial Revolution.